THE IMPORTANCE OF TRAINING IN GOOD FOOD HANDLING PRACTICES FOR FOOD SAFETY IN FOOD AND NUTRITION UNITS (UAN) (Editora Impacto Científico, 2025)
This bibliographic review aimed to identify the food handlers' (FH) knowledge about good handling practices (GHP) in Food and Nutrition Units (FNU). The hygienic-sanitary safety of meals requires the strict application of regulations such as ANVISA's RDC n° 216/2004, aiming to prevent Foodborne Diseases (FBD). The development revealed that the FH is the most critical link in the production chain, with non-compliance with hygienic precepts being the main cause of FBD. Studies in daycares, for instance, showed 100% inadequacy in hand hygiene technique and microbiological contamination in samples, indicating the gap between knowledge and practice. Sanitary legislation makes training mandatory, and the literature reinforces that continuous training, coupled with supervision, is the best alternative to correct failures and promote an effective change in attitude. It is concluded that the solution for improving hygienic-sanitary quality in FNUs lies in implementing an effective program of constant training and supervision, as this is the most efficient means of ensuring food safety and consumer health.DOI: https://doi.org/10.56238/edimpacto2025.090-029